(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the effects of acupuncture combined with therapeutic exercise on pain relief and improvement in shoulder range of motion among patients with simple shoulder periarthritis treated at Thai Binh Traditional Medicine Hospital. Methods: A prospective clinical intervention study with pre- and post-treatment comparisons was conducted among 50 patients diagnosed with simple shoulder periarthritis who received outpatient treatment at Thai Binh Traditional Medicine Hospital from January to June 2025 and met the study eligibility criteria. Results: After 15 days of treatment, clinically meaningful improvements were observed in pain and shoulder range of motion according to the Constant-Murley score. The pain component score increased from 3.9 ± 1.67 to 12.1 ± 2.03 points, indicating reduced pain. Shoulder mobility increased from 13.2 ± 7.76 to 34.27 ± 5.65 points, while shoulder strength/function increased from 10.2 ± 1.50 to 22.57 ± 3.25 points. The SPADI pain score decreased by 30.05 ± 12.17 points. Differences between baseline and post-treatment assessments were statistically significant (p < 0.05). Conclusion: Acupuncture combined with therapeutic exercise appears to be an effective supportive approach for reducing pain and improving shoulder range of motion in patients with simple shoulder periarthritis after 15 days of treatment.